Pharmacokinetics and stability of methoxyflavones from Kaempferia parviflora in Thai native roosters - Chankitisakul, Vibuntita; Authaida, Supakorn; Boonkum, Wuttigrai; Tuntiyasawasdikul, Sarunya (Frontiers in Veterinary Science, 2025)
IntroductionThe present study aimed to characterize the pharmacokinetics and stability of methoxyflavones derived from Kaempferia parviflora (KP) in Thai native roosters after oral administration of a KP ethanolic extract.MethodTwenty-seven male roosters were randomly divided into three groups and received KP extract at different doses of 100, 150, and 200 mg/kg of body weight. Plasma samples were prepared using acetonitrile, ethyl acetate, and a mixture of both to compare the optimal extraction efficiency. Plasma methoxyflavones concentrations were quantified using a validated HPLC method. Pharmacokinetic parameters were calculated using PKSolver. A seven-day stability study assessed methoxyflavones degradation in blood and plasma samples stored at −20°C.Results and discussionThe results showed that methoxyflavones were rapidly absorbed, reaching maximum plasma concentrations (Cmax) ranging from 0.34 to 0.83 µg/mL within 1.17 to 1.83 hours, with a clear dose-dependent relationship. Elimination was slow, with half-lives ranging from 2.03 to 2.60 hours. The study also found that acetonitrile was the most effective solvent for extracting methoxyflavones from blood samples, yielding recovery rates of 73.95%, 81.49%, and 77.5% for 3,5,7,3′,4′-pentamethoxyflavone (PMF), 5,7-dimethoxyflavone (DMF), and 5,7,4′-trimethoxyflavone (TMF), respectively. High stability was observed in blood and plasma over two days (96.6–100%), with significant degradation (84.3–92.6%) after seven days. This study’s results provide valuable insights for optimizing KP extract use as a poultry feed additive by informing appropriate dosage, extraction, and storage procedures to preserve methoxyflavones integrity.